FUNDAMENTALS OF PROFESSIONAL CREATIVITY FUTURE TEACHER - V.V. Ivanova (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the pedagogical creative work as a showing of future teachers readiness for professional activity.